Pet adoption and re-home mobile application - Fong, Yip Kean (2023)
The "Pawfect Home" mobile application was developed to address the pressing need for a streamlined platform dedicated to pet adoption and re-homing. This mobile application prioritizes a user-centric design, ensuring a seamless user interface and experience, complemented by reliable functionality. The key features such as the ability to create and manage adoption listings, share awareness of missing pets, and conduct location-based searches for available pets. Additionally, users can view veterinary services nearby and initiate direct communication with pet owners through the application. The location calculation and detection were dependent on the Google Map API implemented. Moreover, email verification and email domain verification were implemented into the mobile application. To further enhance disposable email domain detection, MailChecker.ai API was implemented to prevent registration of disposable email. The project's development was underpinned by the prototype methodology, which allowed for iterative design, feedback incorporation, and continuous refinement of the application's features and functionalities. Testing methodologies, such as unit and integration testing, further validated the application's functionality and user experience. Furthermore, User Acceptance Testing including SUS and UI Usability test was conducted and the system was evaluated by the users and obtained the recommendations and feedbacks verbally or via the feedback form. While the project was envisioned as a nonprofit tool, the final product demonstration was restricted to showcasing its functionality without real pet data due to time constraints.